Treatment of Acute Infantile Gastroenteritis Dehydration Acidosis with Ringer's Lactate and Glucose-Electrolyte Solution - Hernawan Hernawan; Sunoto Sunoto; Titut S. Pusponegoro; Suharjono Suharjono (Indonesian Pediatric Society, 1978)
Fifty patients hospitalized with severe gastroenteritis - dehydration with acidosis were investigated. The age average was 8 months with the range of 1-18 months. The amount of the Ringer's lactate solution given was as follows:1st hour : 30 ml/kg b.w.the following 7 hours: 70 ml/kg b.w. or 10 ml/kg b.w./hour.After 8 hours on parenteral treatment, the child was given oral solution, either glucose-electrolyte solution or milk formula in Â¼ dilution. The mortality rate was 6% (3 out of 50 patients) i.e. one due to seizures suspected encephalitis, one due to potasium deficiency (K = 2.1 mEq/l) and the third due to dehydration itself because the child was admitted already in a moribund stage (subvinum vitae).